Measurement for Change: Reflections from innovators' experiences with monitoring, evaluation, and learning systems for Early Childhood Development - de Laat, Joost; Radner, James; Holding, Penny; van der Haar, Lotte; Slemming, Wiedaad; Krapels, Joachim; van der Harst, Maria; Raikes, Abbie; Sanou, Anselme Simeon; Dusabe, Caroline (Frontiers in Public Health, 2023)
In this review paper, we explore how on-the-ground Early Childhood Development (ECD) innovators are using monitoring, evaluation, and learning (MEL) systems to guide the design and implementation of ECD programmes, as well as how MEL systems can influence policy and support the achievement of impact at scale. We reflect on articles in the Frontiers series “Effective Delivery of Integrated Interventions in Early Childhood: Innovations in Evidence Use, Monitoring, Evaluation and Learning.” The 31 contributions to the series reflect the breadth and depth of complexity that characterises ECD, including global geographic spread, with studies from Asia, Europe, Africa, and Latin America and the Caribbean. Our synthesis finds that integrating MEL processes and systems into the fabric of a programme or policy initiative can broaden the underlying value proposition. Specifically, ECD organisations sought to design their MEL systems to ensure programmes fit the values, goals, experiences and conceptual frameworks of diverse stakeholders, so that participating makes sense to all. For example, formative, exploratory research identified the priorities and needs of the target population and frontline service providers, and informed the content and delivery of an intervention. ECD organisations also designed their MEL systems to support a shift of accountability toward broader ownership: They included delivery agents and programme participants alike as subjects rather than objects, through active participation in data collection, and by providing opportunities for equitable discussion of results and decision-making. Programmes collected data to respond to specialised characteristics, priorities and needs, embedding programme activities into existing day-to-day routines. Further, papers pointed to the importance of intentionally involving a variety of stakeholders in national and international dialogues to ensure that diverse ECD data collection efforts are aligned and multiple perspectives are considered in the development of national ECD policies. And, several papers illustrate the value of creative methods and measurement tools to integrate MEL into a programme or policy initiative. Finally, our synthesis concludes that these findings align with the five aspirations that were formulated as part of the Measurement for Change dialogue, which motivated the launch of the series.